The Challenges of the Medan City BPBD in Enhancing Community Participation in Disaster Management - Septira Razin Fadhilah; Riska Akila Zahra; Widya Yossi Hutapea; Arnold Jeferson Munthe; Muhammad Aqsha Rangkuti; Diki Pratama; Ilya Zahra; Rini Mayang Sari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the challenges faced by the Badan Penanggulangan Bencana Daerah (BPBD) of Medan City in building community participation in disaster management. Using a qualitative approach with descriptive methods, this research explores experiences and social interactions through in-depth interviews with BPBD staff from various divisions. The findings indicate that although BPBD has systematically implemented disaster management through three phases (pre-disaster, emergency response, and post-disaster), the level of community participation remains low and reactive. The main challenges include weak inter-agency coordination, limited literacy and collective awareness regarding disaster risks, constraints in human resources and funding, and ineffective communication methods used in disaster socialization. Based on community participation and social awareness theories, community participation patterns remain top-down and limited to the implementation stage, not yet encompassing planning and evaluation. This study recommends strengthening education based on local wisdom, developing two-way communication systems, enhancing cross-sector coordination, and implementing community-based disaster management approaches to realize independent and adaptive disaster-resilient communities.